Analytical methods assessment for exchangeable cations analysis in soil: MIP OES appraisement - Jofré, Florencia Cora; Perez, Maria Micaela; Kloster, Nanci Soledad; Savio, Marianela (Taylor & Francis, 2021)
Soil monitoring and research often requires a comparison of laboratory data generated by diverse instruments and in different laboratories to demonstrate the reliability and accuracy of the results. The outcomes of this work highlight a performance comparison among different analytical methods for the determination of calcium (Ca), magnesium (Mg), sodium (Na), and potassium (K), in soil. Five soil samples were used for analytical methods comparison, corresponding to an argentine agricultural soil interlaboratory, and four soil samples from the Pampa region of Argentina were used for analytical application of the instrumental methods. The results obtained with flame atomic absorption and emission spectrometry (FAAS-FAES) and microwaveinduced plasma optical emission spectrometry (MIP OES) were compared to those obtained by conventional analytical methods as complexometric titration and flame photometry. As there were no significant differences between classical methods with instrumental ones, FAAS-FAES and MIP OES were validated following criteria based on international guidelines. Accuracy, precision, linearity, limits of detection and quantification, sensitivity, analytical sensitivity, and working range were evaluated. The results established the satisfactory performance of FAAS-FAES and MIP OES for exchangeable cations. MIP OES is an efficient alternative to FAAS FAES, with wide linear dynamic range, which is advantageous concerning to the concentrations in which these exchangeable cations are found in soils, avoiding sample dilutions. The most remarkable advantage of MIP OES is the low running costs as it does not use flammable and toxic gases. Due to its benefits MIP OES could be recommended as the main analytical method for exchangeable cations determination.